2016
DOI: 10.1097/scs.0000000000002722
|View full text |Cite
|
Sign up to set email alerts
|

Normative Velopharyngeal Data in Infants

Abstract: Identifying normative data related to velopharyngeal muscles and structures may have clinical significance for infants born with cleft palate, especially as they relate to selection of surgical intervention and postsurgical outcomes. Previous studies suggest that patients whose anatomy postsurgically is dissimilar to that of their normative counterparts are at risk for hypernasal speech. However, studies have not documented what constitutes "normal" anatomy for the clinically relevant population-that is, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Thus far, as an imaging tool, MRI has been shown to be reliable, noninvasive, and provides both 2D and 3D views of key velopharyngeal musculature and structures, in both children and adults with cleft conditions. 11,21,22,48,[52][53][54][55][56][57] Furthermore, results of this study indicate that MRI is readily available and of interest for providers on cleft/craniofacial teams. Its use and acceptability, however, remain limited and dependent on the clinical situation in which it is being applied.…”
Section: Future Directions and Opportunities For Clinical Translationmentioning
confidence: 71%
See 3 more Smart Citations
“…Thus far, as an imaging tool, MRI has been shown to be reliable, noninvasive, and provides both 2D and 3D views of key velopharyngeal musculature and structures, in both children and adults with cleft conditions. 11,21,22,48,[52][53][54][55][56][57] Furthermore, results of this study indicate that MRI is readily available and of interest for providers on cleft/craniofacial teams. Its use and acceptability, however, remain limited and dependent on the clinical situation in which it is being applied.…”
Section: Future Directions and Opportunities For Clinical Translationmentioning
confidence: 71%
“…Normative anatomic measures, identified and obtained from MRI, have additionally been reported for varying patient populations. 10,21,[46][47][48][49][50] Additional translational research would likely help to bridge the reported research to practice gap that was noted in this survey and provide data for the efficacy of this modality for velopharyngeal assessments.…”
Section: Barriers To Clinical Translationmentioning
confidence: 96%
See 2 more Smart Citations
“…Secondary analysis of previously collected data was completed. Specifically, participants were recruited as part of separate studies including an infant magnetic resonance imaging (MRI) study (Schenck et al, 2016), a child MRI study (Perry, Kollara, et al, 2018), and an adult MRI study (Perry et al, 2016), all which were conducted for the purpose of analyzing the VP anatomy among a noncleft control group. In accordance with the local institutional review boards, 242 individuals between 4 months and 34 years of age were recruited to participate in this clinical MRI study.…”
Section: Methods Participantsmentioning
confidence: 99%